Analysis of Factors Affecting the Implementation of Accounting in Micro, Small, and Medium Enterprises in Woha District, Bima Regency - Nurfajrian; Lestari, Baiq Anggun Hilendri; Jumaidi, Lalu Takdir (International Journal of Business and Applied Economics, 2024)
This research aims to determine and analyze the influence of education level, business scale, business age, and accounting knowledge on implementing accounting. This research employs a quantitative method. The population in this research consists of 551 Micro, Small, and Medium Enterprises (MSMEs) in Woha District. In contrast, the research sample was obtained using purposive sampling techniques, resulting in a sample size of 50 units. This research comprises four independent variables, namely, education level, business scale, business age, and accounting knowledge, and one dependent variable, the implementation of accounting. The analysis techniques employed include validity testing, reliability testing, normality testing, multicollinearity testing, heteroskedasticity testing, multiple linear regression, the T-test, F-test, and the coefficient of determination. The research results indicate that the level of education, business scale, and business age do not have an impact while accounting knowledge influences the implementation of accounting.